Rotational tree structures on binary trees and triangulations - Pallo, Jean Marcel (Acta Cybernetica, 2006)
A rotation in a binary tree is a simple and local restructuring technique commonly used in computer science. We propose in this paper three restrictions on the general rotation operation. We study the case when only leftmost rotations are permitted, which corresponds to a natural flipping on polygon triangulations. The resulting combinatorial structure is a tree structure with the root as the greatest element. We exhibit an efficient algorithm for computing the join of two trees and the minimum number of leftmost rotations necessary to transform one tree into the other.